2020
DOI: 10.3389/fcvm.2020.00142
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variants at TRPC6 With Chemotherapy-Related Heart Failure

Abstract: Background: Our previous GWAS identified genetic variants at six novel loci that were associated with a decline in left ventricular ejection fraction (LVEF), p < 1 × 10 −5 in 1,191 early breast cancer patients from the N9831 clinical trial of chemotherapy plus trastuzumab. In this study we sought replication of these loci. Methods: We tested the top loci from the GWAS for association with chemotherapy-related heart failure (CRHF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…That study identified transient receptor potential cation channel subunit 6 ( TRPC6) as a potential risk locus for doxorubicin-induced cardiomyopathy in patients with breast cancer ( 19 ). In a follow-up study from our group using 984 patients from the Mayo Clinic Biobank, we replicated the association of toxicity, specifically with the outcome of doxorubicin-induced congestive heart failure (CHF) ( 20 ).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…That study identified transient receptor potential cation channel subunit 6 ( TRPC6) as a potential risk locus for doxorubicin-induced cardiomyopathy in patients with breast cancer ( 19 ). In a follow-up study from our group using 984 patients from the Mayo Clinic Biobank, we replicated the association of toxicity, specifically with the outcome of doxorubicin-induced congestive heart failure (CHF) ( 20 ).…”
Section: Introductionmentioning
confidence: 84%
“…Breeding pairs of B6.129 wild-type (WT) (Cat#101045) and B6.129 Trpc6 whole body knock-out (KO) mice ( 26 ) (Cat#37345) were obtained from the Jackson Laboratory (Bar Harbor, ME). Male and female WT and Trpc6 KO mice (8–10 weeks old), ten mice per group, received either 100 μL intraperitoneally (ip) of control sterile saline or 4 mg/kg/dose doxorubicin for a cumulative dose of 24 mg/kg on days 1, 3, 5, 7, 9, 11 according to ( 20 ). Results were confirmed by repeating each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…A subsequent study by the same group [ 50 ], replicated the association of TRPC6, this time using a case-control analysis with anthracycline-induced congestive heart failure as the outcome (Cases N = 38, Controls N = 984). In this study, the authors performed several levels of analyses which provided evidence for multiple risk variants at TRPC6, firstly suggesting that common non-coding variants within intron 1 and the 5’flanking region of TRPC6 increase risk of cardiotoxicity by their association with increased TRPC6 expression in heart tissue, and secondly that both common and rare missense variants at TRPC6 may increase risk of cardiotoxicity by gain-of-function.…”
Section: Genetic Variants Associated With Anthracycline-induced Cardiotoxicitymentioning
confidence: 96%
“…The significance of these findings is that inhibition of TRPC6 may be a novel cardioprotective therapy, especially for individuals with TRPC6 risk variants. The therapeutic potential was validated in vitro, by demonstration that iPSC-derived cardiomyocytes were protected from doxorubicin-induced apoptosis by pre-treatment with the TRPC6 inhibitor, GsMT×4, and in vivo, by demonstration that GsMT×4 also protected mice from doxorubicin-induced decline in LVEF, global longitudinal strain and fibrosis [ 50 ].…”
Section: Genetic Variants Associated With Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%
See 1 more Smart Citation